Strategies for the development of enzymatic reactions in ionic liquids. (2021)
Ionic liquids are liquid salts at room temperature that have properties as solvents that allows a wide range of applications. Their use in enzymatic reactions is increasing since 1991 because ionic liquids (ILs) serve as a highly efficient reaction medium for biocatalytic reactions that cannot be carried out with traditional solvents such as toluene, methanol or acetone, characterized by high volatility. The present project aims to analyze recent advances on enzymatic reactions in ionic liquids, and their possible applications in obtaining value-added products that may be of interest to the national industry. To achieve this, a systematic review of the literature will be carried out using the Springer link and Science Direct databases available at Universidad ICESI to establish the state of the art. Subsequently, the advantages and disadvantages of traditional ionic liquids and solvents in enzymatic reactions and how their structure and design relate to the properties of ILs are presented. Finally, applications for biofuel production using ILs were shown. Hydrophobic ionic liquids were found to have potential as reaction media with enzymes in different applications due to high conversion rates, high selectivity and enhanced enzymatic stability.